Prognostic Analysis and Influencing Serum Biomarkers of Patients With Resectable Pancreatic Adenosquamous Cancer - Shi, Yusheng; Wang, Xinjing; Wu, Weize; Xie, Junjie; Jin, Jiabin; Peng, Chenghong; Deng, Xiaxing; Chen, Hao; Shen, Baiyong (Frontiers in Oncology, 2021)
Objectives There are few reports about the survival rate of patients with pancreatic adenosquamous cancer (PASC). This study evaluated and analyzed prognostic factors of patients with resectable pancreatic adenosquamous cancer (rPASC), which might fulfill the blank in the research of PASC. Methods In this study, we identified and analyzed 62 patients who were diagnosed with rPASC from January 2013 to May 2019 at the Pancreatic Disease Center of the Shanghai Ruijin Hospital affiliated with Shanghai Jiaotong University School of Medicine. Age, sex, BMI, tumor position and other important demographic data were collected and analyzed. The follow-up was updated by December 31th, 2019 with a median follow-up of nine months. Results Among the 55 patients, 23 (41.8%) patients were female, and the mean age was 62.0±10.3 years. The median overall survival (OS) time was 10±2.1 months, and the median disease-free survival (DFS) time was 4±0.9 months. The 1-year, 3-year and 5-year survival rates were 40.9%, 17.5% and 11.6%, respectively. The multivariate analysis showed that normal serum level of Ca-199 (HR=0.464, 95%CI=0.222-0.970, P=0.041) and Ca125 (HR=0.441, 95%CI=0.233-0.835, P=0.012) were independent favorable prognostic factors. Conclusion Patients with rPASC had poor survival. The 5-year survival rate was only 11.6%. Normal serum levels of Ca-199 and Ca-125 were independent favorable prognostic factors that predicted prognosis.